Microstructural features and oxidation resistance of (Ti, Zr)C solid solution nanofibers fabricated using polymeric precursors. Issue 18 (15th December 2019) - Li, Fuping; Wang, Weihua; Dang, Wei; Xu, Zhuoli; Zhao, Kang; Tang, Yufei
Abstract: Solid solution ceramics of transition-metal carbides possess higher hardness and better oxidation resistance in comparison with monolithic transition-metal carbides. In this communication, (Ti, Zr)C solid solution nanofibers were successfully fabricated through electrospinning using polymeric precursors. The effect of n (Ti)/n (Zr) on the microstructure of nanofibers was investigated. Complete solid solutions of (Ti0·8 Zr0.2 )C and (Ti0·75 Zr0.25 )C were formed at 1600 °C when the value of n (Ti)/n (Zr) equal to 4 and 3, respectively. With a decrease in n (Ti)/n (Zr) to 2, Ti-rich and Zr-rich phases appear. The oxidation resistance of the fabricated nanofibers was tested by a non-isothermal method. The oxidation temperature of (Ti, Zr)C solid solution nanofibers is improved compared to TiC nanofibers.